Chemical molecular‐based approach to overcome multidrug resistance in cancer by targeting P‐glycoprotein (P‐gp) - Zhang, Hang; Xu, Haiwei; Ashby, Charles R.; Assaraf, Yehuda G.; Chen, Zhe‐Sheng; Liu, Hong‐Min (Medicinal research reviews, 2021)
Multidrug resistance (MDR) remains one of the major impediments for efficacious cancer chemotherapy. Increased efflux of multiple chemotherapeutic drugs by transmembrane ATP‐binding cassette (ABC) transporter superfamily is considered one of the primary causes for cancer MDR, in which the role of P‐glycoprotein (P‐gp/ABCB1) has been most well‐established. The clinical co‐administration of P‐gp drug efflux inhibitors, in combination with anticancer drugs which are P‐gp transport substrates, was considered to be a treatment modality to surmount MDR in anticancer therapy by blocking P‐gp‐mediated multidrug efflux. Extensive attempts have been carried out to screen for sets of nontoxic, selective, and efficacious P‐gp efflux inhibitors. In this review, we highlight the recent achievements in drug design, characterization, structure–activity relationship (SAR) studies, and mechanisms of action of the newly synthetic, potent small molecules P‐gp inhibitors in the past 5 years. The development of P‐gp inhibitors will increase our knowledge of the mechanisms and functions of P‐gp‐mediated drug efflux which will benefit drug discovery and clinical cancer therapeutics where P‐gp transporter overexpression has been implicated in MDR.